The foreign direct investment-Export performance nexus: An ARDL based empirical evidence from Ethiopia - Teamrat Kahssay Gebremariam; Ying Sun (Cogent Economics & Finance, 2022)
Ethiopia is one of the top FDI destinations in Africa and the leading FDI receiver in east Africa. However, little is known about the direct impact of the FDI on the Ethiopian export performance. This study was conducted to fill this gap. As a result, the main objective of this study was to examine the empirical relationship between foreign direct investment and export performance in Ethiopia by using an annual time series data for the period 1992-2018. The analysis was based on the autoregressive distributed lag (ARDL) model. The long-run model result, which was estimated after a proper application of pre-estimation tests, displayed that the relationship between FDI and export performance was insignificant. The estimated long-run equation also revealed that an increase in the real GDP resulted in an improved export performance in Ethiopia. The coefficient of the real effective exchange rate index in the long-run equation implies that depreciation of the exchange rate improves the export performance. According to the short-run and long-run estimation results, the study provides recommendations to improve Ethiopian export performance. First, national economic policies have to be directed toward keeping the overall health of the economy safe and achieving fast and sustainable growth. Second, with regarding to exchange rate management, long-term effects need to be considered. Finally, attracting more foreign firms to engage in value addition activities for the primary agricultural products would also play a role in enhancing the export performance.
Keywords: 330; Export Performance; FDI Inflows; Autoregressive Distributed Lag; Bounds Test; Ethiopia